Postnatal Posterior Fossa Arachnoid Cyst: A Developmental Etiology to Be Considered - Ramachandran, Thiynesvaran; Valayatham, Vijayan; Ganesan, Dharmendra (Asian Journal of Neurosurgery, 2022)
Intracranial arachnoid cyst is the most common cystic congenital anomaly in the brain. In this study, we discuss a pregnancy that had serial fetal ultrasound scans throughout the pregnancy and a fetal anomaly scan at 24 weeks of gestation that was normal. The child was born healthy with normal development, but 12 months onward the head began to enlarge. The magnetic resonance imaging of the brain showed a large posterior fossa arachnoid cyst with hydrocephalus. We discuss the postulation to explain this pathogenesis of the cyst. This case highlights that not all symptomatic arachnoid cysts are congenital despite the manifestation being as early as infancy.
Keywords: posterior fossa arachnoid cyst; fetal ultrasound; arachnoid cyst; pathogenesis; acquired; congenital